The limits of literature as liberation: Colonialism, governmentality, and the humanist subject - Greedharry, M (Management learning, 2021)
Scholars in both the humanities and management remain attached to the idea that literature will set us free. Whether this is because literary text seems unconstrained by our epistemes or reading literature offers a practice through which we will be able to shape ourselves into the people we want to be, many of us understand literature as something that offers us a chance to emancipate ourselves from the regime of knowledge we have now. Nevertheless, as the history of literature as colonial governmentality suggests, literature and literary study have been crucial forms of knowledge-power for creating and maintaining organizational structures as well as producing the willing subjects that make those structures work. This being so, how is it that are we still interested in using literature to make “better” people, whether the people in question are ”better” managers or their subordinates, rather than reorganizing literary study in the contemporary university?